Assessment of early supplier involvement in product development in Malaysia food industry - Yap, Jessica (2016)
Early supplier involvement (ESI) benefits product development in several ways. However, many food industries do not know the advantages of ESI and therefore do not utilize it. Therefore, it is vital for the food industries to understand the contribution and effectiveness of ESI in product development in Malaysia food industry. This study aims to analyze contribution of ESI in early product development and evaluate effectiveness of ESI in product development in Malaysia food industry. Data were collected by using a set of survey questionnaires among the managers in food industries at Kuala Lumpur and Selangor area. Results from the study indicated that the most significant contribution of suppliers in early product development in Malaysia food industry is new technologies identification. Besides, product cost ranked the most effective criteria of ESI in product development in Malaysia food industry. The results provided sufficient insight and understanding into the contribution of ESI as well as look deeply into the effectiveness of ESI in product development in Malaysia food industry.